Análise e projeto de um boost PFC + ZAHB para luminárias led CA-CC - Pedroso, Douglas Araujo (2021)
This master’s thesis presents the analysis and design of a two-stage 100W and universal input ac-dc LED driver. The driver’s front-end topology is composed by a PFC (Power Factor Corrector) boost converter whereas the back-end deploys and Zeta Asymmetrical Half-Bridge converter (ZAHB). The document complies a short overview on the LED general concepts and relevant metrics and standards followed by a deep literature review which includes several different topologies classified by their number of stages and disposition. A trade-off analysis considering a myriad of relevant characteristics for a LED driver is performed among all the candidate topologies and, as the outcome, the PFC boost + ZAHB two-stage combination is selected. A detailed design process and analysis on both topologies is presented and the point of operation selection is done based on balancing volume and efficiency of each stage. Finally, outcome results from the design process are presented in order to validate it and show the driver’s compliance with the most relevant standards on energy and light quality.